Attitudes and practices of gynecologists in Jaipur toward management of menopause - Shuchita Meherishi; Sunila Khandelwal; M L Swarankar; Prabhleen Kaur (Wolters Kluwer Medknow Publications, 2010)
Background: In earlier days, hormone replacement therapy (HRT) was recommended for menopause symptoms and also gained much popularity. However, the Women's Health Initiative (WHI) studies suggested an increased risk of cardiovascular and Alzheimer's disease. These findings led to a dramatic decrease in hormone therapy (HT) prescriptions all over the world. However, the WHI conclusions remain debatable especially because of contradictory results from antecedent studies. Inspite of these controversies, post-WHI, most gynecologists refrain from prescribing MHT (menopausal hormone replacement therapy, MHT). Furthermore, many Indian gynecologists prefer to prescribe alternative treatments that would help alleviate symptoms and thus avoid HRT. We decided to carry out a survey and document the current opinions regarding indications of HRT and alternative therapies and prescribing practices of Jaipur-based gynecologists. Objective: This study was designed to find out the current attitudes and practices of gynecologists (Jaipur) towards management of menopause. Materials and Methods: A questionnaire concerning attitudes, management strategies, and use of HT was mailed out to gynecologists, and they are asked to complete the questionnaire. Data were analyzed using the total number of respondents (n = 321). The results were analyzed using a simple percentage method as this was most suitable for this kind of studies. Results: From the results, 69.04% gynecologists were currently prescribing MHT. Hot flashes were the most common indication for MHT prescriptions and 78.57% were familiar with controversies surrounding WHI study. Also, 61.9% would consider using MHT for themselves. Alternative therapy was adopted by 83.48% in their prescribing practice. The reason cited by 71% for preferring alternative therapies was that it was safer and less controversial. Conclusions: The prescribing practices of Jaipur gynecologists in lieu of ongoing controversies surrounding HT have shifted and now also support alternative therapies for menopause management. In this era of phasic prescriptions, for immediate relief of hot flashes and mood swings, MHT was favored. However, for long-term management of women with poor compliance, alternative therapies were considered a safer option.